Penggunaan Media Visual dalam Meningkatkan Aktivitas dan Keterampilan Menulis Laporan - Ratna Sari Dewi Pohan; Yuhelmi Yuhelmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to describe the improvement of student report writing activities and skills through visual media. This research data in the form of qualitative data and quantitative data. Research procedures through stages: 1) observation and identification of problems, 2) pre-action activities, 3) planning research, 4) choosing a process approach using visual media to increase the activity and value of report writing skills, 5) making three-dimensional visual learning media to be projected through the LCD of the projector, 6) making observation sheets, 7) implementing research (observation, analysis and reflection). Research activities were carried out 2 times without using visual media and using visual media. Data collection was carried out by 2 researchers with observers. The results of the study found that after the research was conducted, it appeared that there was an improvement in student processes and grades. The results showed an increase in activity indicators (an average of 60 with sufficient qualifications (before the use of the media), to 80 with good qualifications (after the use of the media). Improved values ​​can be seen from an average of 54.17 (before) with almost enough qualifications being 76.25 with good qualifications (after). This explains that visual media can improve student activities and grades in writing reports based on visual objects. Keywords: Activities, Skills, Writing, Reports, Visual Media